Kiprah Politik Dan Sejarah Organisasi Muhammadiyah di Indonesia - Suryana, Cecep (Jurnal Ilmu Dakwah, 2009)
The History of politics development in Indonesia, the really cant forget the role ofÂ  muslim people groups in national politics stage, one of them named Muhammadiyah organization. This big organization found since 1912 by KH. Ahmad Dahlan with struggles main basic, bringing muslim people back to really confidence, which is that pure leaning to Qurâ an and hadits and not to another one. Politic action formâs manifested on three movement patterns: revivalism, secularism and modernism. In revivalism pattern, Muhammadiyah struggleâs have given its contribution to BPUPKI about year 1945 as alternative solution divides state basics. secularism is not amends, meanwhile modernism declares that Islamic teaching can be fused by politics or state problem can be carried on concurrently so forms symbiotic relationship among religion with state or politics.